2019
DOI: 10.1111/his.13764
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of RCAN2 production in gastric carcinoma

Abstract: Aims Gastric cancer (GC) is one of the leading causes of cancer‐related death worldwide. Genes expressed only in cancer tissue may be useful biomarkers for cancer diagnosis and therapeutics. The aims of the present study were to analyse regulator of calcineurin 2 (RCAN2) in a large number of GCs, and to investigate how these expression patterns correlate with clinicopathological parameters and various markers. Methods and results An immunohistochemical analysis of RCAN2 in 207 GC tissue samples showed that 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…TGF-β regulates gene expression by SMAD-mediated signal transduction [39]. TGF-β reportedly induces CPE, TNC, TAGLN, CSRP2, and COL4A5 expression [28,33,40]. Therefore, it is suggested that TGF-β/SMAD pathway-mediated promotion of gene transcription might underly intramuscular fat formation in Japanese Black cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β regulates gene expression by SMAD-mediated signal transduction [39]. TGF-β reportedly induces CPE, TNC, TAGLN, CSRP2, and COL4A5 expression [28,33,40]. Therefore, it is suggested that TGF-β/SMAD pathway-mediated promotion of gene transcription might underly intramuscular fat formation in Japanese Black cattle.…”
Section: Discussionmentioning
confidence: 99%
“…These CSRPs act as transcription factors in the nucleus and promote cell differentiation in various cell types. CSRP2 expression is reportedly induced by TGF-β [33], an essential gene for epithelialmesenchymal conversion [28]. Although CSRP1, CSRP2, and CSRP3 were highly expressed in intramuscular fat tissue (Figure S2), their detailed function is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, Rcan2 was originally recognized as a thyroid hormone-responsive gene in human skin fibroblasts [ 28 ] and then highlighted as a mediator of CaN [ 29 , 30 ]. More interestingly, alteration in Rcan2 levels was previously found to be correlated with the development of tumor [ 31 ], whereas Rcan2 is also known to regulate the obesity progression via a mechanism-independent of leptin signaling [ 32 , 33 ]. Interestingly, the RCAN protein family has vital roles to confer in regulating inflammation [ 34 ]; for example, Rcan1 serves a negative regulator of inflammation in response to respiratory tract infections [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is one of the most common malignant tumors globally and the second leading cause of cancer death (1). At the time of diagnosis, about 30% of patients with gastric cancer have progressed to an advanced stage (2). Chemotherapy is one of the standard treatments for most advanced gastric cancers.…”
Section: Introductionmentioning
confidence: 99%